Investigating the effect of poly-l-lactic acid nanoparticles carrying hypericin on the flow-biased diffusive motion of HeLa cell organelles. (19th July 2017) - Penjweini, Rozhin; Deville, Sarah; Haji Maghsoudi, Omid; Notelaers, Kristof; Ethirajan, Anitha; Ameloot, Marcel
Abstract: Objectives: In this study, we investigate in human cervical epithelial HeLa cells the intracellular dynamics and the mutual interaction with the organelles of the poly-l -lactic acid nanoparticles (PLLA NPs) carrying the naturally occurring hydrophobic photosensitizer hypericin. Methods: Temporal and spatiotemporal image correlation spectroscopy was used for the assessment of the intracellular diffusion and directed motion of the nanocarriers by tracking the hypericin fluorescence. Using image cross-correlation spectroscopy and specific fluorescent labelling of endosomes, lysosomes and mitochondria, the NPs dynamics in association with the cell organelles was studied. Static colocalization experiments were interpreted according to the Manders' overlap coefficient. Key findings: Nanoparticles associate with a small fraction of the whole-organelle population. The organelles moving with NPs exhibit higher directed motion compared to those moving without them. The rate of the directed motion drops substantially after the application of nocodazole. The random component of the organelle motions is not influenced by the NPs. Conclusions: Image correlation and cross-correlation spectroscopy are most appropriate to unravel the motion of the PLLA nanocarrier and to demonstrate that the rate of the directed motion of organelles is influenced by their interaction with the nanocarriers. Not all PLLA-hypericin NPs are associated with organelles.